Double matching: Social contacts in a labour market with on-the-job search - Anna Zaharieva (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
This paper develops a labour market matching model with heterogeneous firms, on-thejob search and referrals. Social capital is endogenous, so that better connected workers bargain higher wages for a given level of productivity. This is a positive effect of referrals on reservation wages. At the same time, employees accept job offers from more productive employers and forward other offers to their unemployed social contacts. Therefore, the average productivity of a referred worker is lower than the average productivity in the market. This is a negative selection effect of referrals on wages. In the equilibrium, wage premiums (penalties) associated with referrals are more likely in labour markets with lower (higher) productivity heterogeneity and lower (higher) worker's bargaining power. Next, the model is extended to allow workers help each other climb a wage ladder. On-the-job search is then intensified and wage inequality is reduced as workers employed in high paid jobs pool their less successful contacts towards the middle range of the productivity distribution.
Keywords: J23; J31; J64; 330; social networks; referrals; on-the-job search; social capital; wage inequality